Toward “Reciprocal Legitimation” between Shakespeare’s Works and Manga - Yoshihara, Yukari (Multicultural Shakespeare: Translation, Appropriation and Performance, 2016)
In April 2014, Nihon Hoso Kyokai (NHK: Japan Broadcasting Company) aired a short animated film titled “Ophelia, not yet”. Ophelia, in this animation, survives, as she is a backstroke champion. This article will attempt to contextualize the complex negotiations, struggles and challenges between high culture and pop culture, between Western culture and Japanese culture, between authoritative cultural products and radicalized counterculture consumer products (such as animation), to argue that it would be more profitable to think of the relationships between highbrow/lowbrow, Western/non-Western, male versus female, heterosexual versus non-heterosexual, not simply in terms of dichotomies or domination/subordination, but in terms of reciprocal enrichment in a never-ending process of mutual metamorphoses.